Comparative Study of Sperm Concentration in Pakistani Men - Muhammad Owais Ahmad , Umay Kalsoom,Inam-ul-Haq (Journal of Rawalpindi Medical College, 2015)
Background: To determine the sperm concentration of proven fertile males and to compare this with that of infertile males. Methods: In this comparative study semen samples of fifty husbands of pregnant women attending the antenatal clinic were obtained. Another fifty infertile men were inducted into the study as a control group. Inclusion criteria for the proven fertile males was the pregnancy achieved within one year of marriage with successful coituses. For the infertile males the inclusion criteria was failure to achieve pregnancy without the use of assisted reproductive techniques, with no infertility factors in the female partner. The exclusion criteria was secondary infertility, tuberculosis, mumps, orchitis, any chronic debilitating illness, varicoceole, sexually transmitted diseases, any drug affecting male fertility e.g. beta-blockers, anti-neoplastic agents etc. The semen samples were obtained after 3 to 4 days of sexual restraint at the laboratory. A drop of 10 – 15 μl of semen in the center of Makler’s chamber was placed and covered with cover glass.Total number and motile number of sperms in 10 squares of the grid under phase contrast microscope at x20 magnification were counted. Three observations were taken and an average number of total sperm count and motile sperm count were calculated. This gives number of sperms x 106 /ml. Chi- square test was used. P-value <0.05 was considered statistically significant. Results: The total sperm count ranged from 20 to 179 millions/ml in the proven fertile male group and from 0 to 169 millions/ml in the infertile group. Total sperm count was significantly higher in proven fertile males as compared to the infertile males group (p < 0.004) Conclusion: Sperm concentration is useful in in-vivo situation to find males having a greater chance of infertility problem